Bleedings from acute gastric and duodenum ulcers in clinical practice (Texas Journal of Medical Science, 2024)
There are presented the reasons of Sharp stomach ulcer bleeding (or intensification) duodenal ulcer or ulcer bleeding while applicating glucocorticoid hormones on patients with thrombocytopenic purpura. It is recommended to change GCH application from per os to inhalation or intravenous injection. It is proved that there is a direct connection between recommendation to endoscopic investigation and bleeding, stomach ulcer and duodenal ulcer from the quantity of thrombocytes. Ans it is also recommended to make endoscopic investigation on thrombocytopenic purpura during clinical remission